Rosalind Franklin Society Proudly Announces the 2022 Award Recipient for Health Equity (Mary Ann Liebert, 2023)
The Rosalind Franklin Society (RFS), in partnership with Mary Ann Liebert, Inc., publishers, enthusiastically congratulate our distinguished recipient of the 2022 annual RFS Award in Science for this journal, which recognizes the outstanding research and published work of women and underrepresented minority scientists, physicians, and engineers. Lily K. Villa, Shakthi Bharathi Murugesan, Lora A. Phillips, Alexandria J. Drake, and Nathan A. Smith, ?Mobile Pantries Can Serve the Most Food Insecure Populations,? Health Equity 6, no. 1 (December 2022): 49?54, http://doi.org/10.1089/heq.2021.0006. Abstract Food insecurity is a crisis in the United States and is particularly dire in Maricopa County, Arizona, where 1 in 5 children experience food insecurity, and >1 in 10 residents experience poverty. Mobile food pantries can help; however, there is minimal knowledge about how communities utilize these food distributors. Research on people aged 60+ years and immigrant populations shows that these populations are especially vulnerable to food insecurity. This study utilized data from a food pantry called ?Phoenix Rescue Mission? (PRM) on food insecure people's use of PRM's mobile and brick-and-mortar pantries, as well as census data. Using GIS mapping and a multinomial logistic regression model, this research identifies how different demographic groups engage with PRM's brick-and-mortar or mobile pantries. Findings indicate that people aged 60?80 years and immigrant people of color are more likely to use both mobile and brick-and-mortar pantries. This research suggests that mobile pantries can reach the most food insecure populations and local nonprofits and governments can consider implementing mobile pantries to reach food insecure communities. Biosketch Lily Villa is a PhD candidate who will defend her dissertation in spring 2023 in applied sociocultural anthropology. She engages her research for social justice activism. Her main area of research is intergenerational community development. Prior to graduate school, Villa worked for 10 years in social services for youth education and development. She also has a graduate certificate in nonprofit leadership and management, and she currently works for the Arizona Coalition to End Sexual and Domestic Violence as a grant management specialist. Villa has a deep passion for fighting against oppression. As an activist scholar, she is committed to helping build the resources necessary to ensure that everyone in Arizona can stay safe, healthy, and happy. All of her research is community-embedded, coauthored with local community leaders, and is an effort to move toward a kinder, more equitable, and loving world.